Malassezia in Inflammatory Bowel Disease: Accomplice of Evoking Tumorigenesis - Yang, Qiyu; Ouyang, Jing; Pi, Damao; Feng, Li; Yang, Jiadan (Frontiers in Immunology, 2022)
Accumulating evidences indicate that patients with inflammatory bowel disease (IBD) have a significantly high risk of developing different cancers, while the exact mechanism involved is not yet fully understood. Malassezia is a lipid-dependent opportunistic yeast, which colonizes on mammalian skin and internal organs. Besides, dysbiosis in fungal communities accompanied by high level of Malassezia are fairly common in inflammatory diseases such as IBD and various cancers. In cancer patients, higher levels of Malassezia are associated with worse prognosis. Once it is ablated in tumor bearing mice, their prognostic conditions will be improved. Moreover, Malassezia manifests multiple pro-inflammatory biological properties, such as destruction of epithelial barrier, enrichment of inflammatory factors and degradation of extracellular matrix (ECM), all of which have been reported to contribute to tumor initiation and malignant progression. Based on these facts, we hypothesize that high levels of Malassezia together with mycobiome dysbiosis in patients with IBD, would aggravate the micro-ecological imbalance, worsen the inflammatory response, and further promote tumorigenesis and deterioration. Herein, we will discuss the detrimental properties of Malassezia and explore the key role of this fungus in the correlation between IBD and cancer, in order to take early surveillance and intervention to minimize the cancer risk in individuals with IBD.